PENGARUH LATIHAN INTERVAL TRAINING TERHADAP DAYA TAHAN KARDIORESPIRATORI ATLET ANGGAR PUTRA JUNIOR BENGKALIS FENCING CLUB - Floriana, Atika; ', Slamet; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: As for the problem of this research is that the lower cardiorespiratory endurance of fencing men junior athlete of Bengkalis fencing club is considered to be poor. At the time athlete endurance did the test endurance with(Tes Balke)only one athlete take a distance of the most on the count Vo2max athlete at 46.54 based on standard ranges 49-43 pronounced lack. Forms of this research is the experimental treatment (Experimental), with a sample of men junior athlete of Bengkalis fencing club, the data in this research is the entire sample of 6 people. As a variabe free is exercise Interval training(X) and the variables bound (Y) cardiorespiratory endurance. The data was teken through reetes and posttes before and after doing exercise Interval training it to improve the ability of the cardiorespiratory endurance. The instruments used in this research is to test run multi stage (bleep test), which aims to measure the maximum oxygen consumption capability (Vo2max). After that, the data is processed with statistical, normality test with lilifors test at significance level α (0.05). The hypothesis is the effect of exercise Interval training to the cardiorespiratory endurance. Based on t test analysis produces Ttabel Thitung of 5,114 and 1,943, meaning Thitung> Ttabel. Based on the analysis of statistical data, there are an average Pree-test of 46,8 and an average post-test 48,6, then the data is normal. Thus, there The Effect Interval Training Exercise Toward Cardiorespiratory Endurance Of Fencing Men Junior Athlete Of Bengkalis Fencing Club.Keywords : Interval Training, Cardiorespiratory Endurance.